ANTIOXIDANT ACTIVITY, TOTAL POLYPHENOLS AND TANNINS CONTENTS OF TARA EXTRACTS, CAESALPINIA SPINOSA - Avilés, R. (2010)
The physicochemical properties (antioxidant activity, total polyphenols and tannins contents) of tara extracts have been obtained. Samples were taken from the pod of tara (powder, fiber, seed coat and the inside of the seed) by maceration and Soxhlet extraction. All extracts have high antioxidant activity with an IC50 between 10 and 121 µg/mL. The total polyphenol content varies between 40 and 150 mg GAE/g of sample and the tannins content varies between 22 and 80%.